Effectiveness of occupational safety and health management system on knowledge, attitude, and practices of occupational safety among laboratory staff in Makkah Hospitals, Saudi Arabia - Almutairi, Nayef Shabbab F (2020)
Health-related issues of laboratory staff have become a major concern for hospital managers. Occupational injuries and illnesses among medical laboratory technicians would usually result from the exposure to several occupational hazards. The lack of safety measures will increase the health risks of the laboratory staff as well as increasing the operational costs and turnaround time, besides from having an impact on their loyalty and satisfaction. There are different factors that contribute to the prevalence of occupational hazards in medical laboratories, among them is the lack of education and knowledge among staff. Therefore, adequate awareness, knowledge, training, and compliance with OSHMS are important issues in laboratory setting worldwide, especially in developing countries. The general objective of this study is to determine the effectiveness of Occupational Safety and Health Management System (OSHMS) on occupational safety and health system of laboratory staff in Makkah hospitals, Saudi Arabia. This research was conducted using a mixed method which includes both qualitative and quantitative methods. Two approaches were used in the qualitative assessment which are HIRARC and OSHMS in evaluating the risk level and control measures in occupational hazards, as well as the compliance to OSHMS. The quantitative assessment involved the use of quasi-experimental repeated measure with the controlled group, which was conducted in Makkah city hospitals. A questionnaire was developed and validated through a panel of experts while a pilot study was performed to measure the knowledge, practices, and respondents’ attitude towards occupational safety and incidents. The study was conducted in Makkah with three hospitals selected for the case study. From the three hospitals, two hospitals with a 477-bed capacity each were combined to represent the control group while one hospital with a 373-bed capacity represented the intervention group. The sample size was calculated using power analysis. 70 respondents were randomly selected from the intervention group population while 70 respondents from the control group population were matched with the respondents from the intervention group. Baseline, post intervention and follow up 1 and 2 (after 3 and 6 months) were conducted to evaluate the effects of intervention on the respondents’ safety. Validated educational intervention in the form of lectures were implemented after the collection of the baseline data. The data were analyzed using the SPSS 22 software as well as descriptive statistics such as mean and standard deviation. Frequency analysis was applied for the respondents’ demographic variables as well as the qualitative part related to HIRARC and OSHMS in both the control and experimental groups where the data obtained were compared using the Chi square test. For the second phase of this study, the quantitative method was used where the independent t test and the two-way repeated measure MANOVA/MANCOVA were applied. The results showed that among all three hospitals, 19.3% of the risk and control measures related to occupational hazards was at a low risk, 78.2% at a moderate level while the remaining 2.5% was at a high level. The results for incidence indicated that 70.7% of the staff had reported the incidence/ accidents to the authorized personnel while the other 29.3% of the incidence were never reported while the remaining 30.9% of the staff were exposed to at least one occasion of injury in the lab. The results of the repeated measure MANCOVA analysis for both groups across time showed that there are significant differences between the two groups (control and intervention) in terms of knowledge, attitude, and practices of occupational safety among the laboratory workers at 0.05 level of significance. Besides that, the frequency of being exposed to injury in the intervention group was reduced from 30.2% to 12.9% which is statistically significant. Educational intervention lectures have been found to be effective in reducing incidence rate and enhancing the safety of laboratory staff. The intervention was also effective in enhancing the respondents’ knowledge, attitude and practices which finally affect their safety. Thus, the provision of a regular pattern of feasible educational meetings/classes for the staff and the determination of their level of knowledge, practices and attitude at various times is very important, which can be achieved through the use of the validated questionnaire provided in this work, as an easy and useful instrument.